Polyvinylpyrrolidone-Based Bio-Ink Improves Cell Viability and Homogeneity during Drop-On-Demand Printing - Ng, Wei Long (2018)
Drop-on-demand (DOD) bioprinting has attracted huge attention for numerous biological applications due to its precise control over material volume and deposition pattern in a contactless printing approach. 3D bioprinting is still an emerging field and more work is required to improve the viability and homogeneity of printed cells during the printing process. Here, a general purpose bio-ink was developed using polyvinylpyrrolidone (PVP) macromolecules. Different PVP-based bio-inks (0%–3% w/v) were prepared and evaluated for their printability; the short-term and long-term viability of the printed cells were first investigated. The Z value of a bio-ink determines its printability; it is the inverse of the Ohnesorge number (Oh), which is the ratio between the Reynolds number and a square root of the Weber number, and is independent of the bio-ink velocity. The viability of printed cells is dependent on the Z values of the bio-inks; the results indicated that the cells can be printed without any significant impairment using a bio-ink with a threshold Z value of ≤9.30 (2% and 2.5% w/v). Next, the cell output was evaluated over a period of 30 min. The results indicated that PVP molecules mitigate the cell adhesion and sedimentation during the printing process; the 2.5% w/v PVP bio-ink demonstrated the most consistent cell output over a period of 30 min. Hence, PVP macromolecules can play a critical role in improving the cell viability and homogeneity during the bioprinting process.